Cardiovascular risk in patients with scarring and nonscarring alopecias: Assessing the current state of evidence - Rachel Sally; Camille Robinson; Seth J. Orlow; Jerry Shapiro; Michael Garshick; Kristen Lo Sicco (JEADV Clinical Practice, 2024)
Abstract Alopecia is traditionally classified into scarring and nonscarring subtypes, with etiopathologies ranging from androgen‐mediated to immuno‐inflammatory. Over 50% of men and almost 50% of women will experience some form of hair loss in their lifetime. Given this prevalence and the psychosocial significance of hair, understanding the pathophysiology and comorbidities of different types of hair loss is imperative. Other proinflammatory dermatologic disorders, such as psoriasis, are recognised to have systemic manifestations including an increased risk of cardiovascular (CV) disease, and are now considered CV risk‐enhancing conditions. With increased recognition of the importance of systemic inflammation in promoting atherosclerosis, high prevalence, and improved treatment strategies, there is increased interest in establishing whether a similar association between alopecia and cardiovascular disease (CVD) exists. In this manuscript, we aim to review the current literature regarding CV risk in androgenic alopecia (AGA) and alopecia areata (AA). Additionally, we review the literature for cicatricial alopecias and highlight the need for more research into their potential associations with CV risk. Evidence from the identified AGA publications suggests an association of AGA with CV risk factors including hypertension, dyslipidemia, and insulin resistance, as well as with coronary artery disease. For AA, most of the identified studies found an association between AA and CV risk, though the relationships were not always statistically significant. Research on cicatricial alopecias and CV risk is limited and often contradictory. There is great need for more studies regarding the association between various types of alopecia and the development of CVD, and potential mechanisms. Particularly needed are more studies of cicatricial alopecias and potential associated CV risk. While some literature suggests that patients with alopecia have an increased risk of CVD, the lack of concrete evidence represents a notable gap in our current understanding.